NUTRITIONAL STATUS AND ASSOCIATED FACTORS AMONG CHILDREN LESS THAN FIVE YEARS OF AGE IN TEHSIL ZARGHOON TOWN, DISTRICT QUETTA, BALUCHISTAN - Achakzai, Pairzo; Khan, Rukhsana (Journal of Ayub Medical College Abbottabad, 2016)
Background: Globally, more than one-third of mortalities in children under five years of age are attributable to malnutrition. The prevalence of malnourished children in Pakistan is inclining. A knowledge gap exists due to availability of limited literature about the nutritional status of children in rural Baluchistan. Therefore, this study assessed the magnitude and factors associated with nutritional status of children of less than five years of age in Tehsil Zarghoon Town of District Quetta. Methods: A community based cross-sectional study was conducted in two rural union councils of Tehsil Zarghoon Town of District Quetta, selected randomly. An existing questionnaire was modified and three research assistants were hired to collect data from 104 children, selected systematically. Data analysis was done using SPSS-20 and World Health Organization (WHO) Anthro software. Results: Results showed that the proportion of stunting and wasting in children comprising the study population was 48.1% and 9.7% respectively. A significant association was demonstrated between stunting and wasting and socio-demographic characteristics, child health characteristics and maternal health characteristics. Conclusion: It was concluded that the nutritional status of children under five years of age inTehsilZarghoonTown of districtQuetta was unsatisfactory. Thus, community mobilization and incorporation of nutrition related activities in primary health care are recommended.